Fabrication of Lateral Polysilicon Gap of Less than 50nm Using Conventional Lithography - Dhahi, Th. S.; Hashim, U.; Ali, M. E.; Ahmed, N. M.; Nazwa, T. (Hindawi Publishing Corporation, 2011)
We report a thermal oxidation process for the fabrication of nanogaps of less than 50 nmin dimension.Nanogaps of this dimension are necessary to eliminate contributions from double-layer capacitance in the dielectric detection of protein or nucleic acid. The method combines conventional photolithography and pattern-size reduction techniques. The gaps are fabricated on polysiliconcoated silicon substrate with gold electrodes. The dimensions of the structure are determined by scanning electron microscopy (SEM). An electrical characterization of the structures by dielectric analyzer (DA) shows an improved conductivity as well as enhanced permittivity and capacity with the reduction of gap size, suggesting its potential applications in the detection of biomolecule with very low level of power supply. Two chrome Masks are used to complete the work: the first Mask is for the nanogap pattern and the second one is for the electrodes. An improved resolution of pattern size is obtained by controlling the oxidation time. The method expected to enable fabrication of nanogaps with a wide ranging designs and dimensions on different substrates. It is a simple and cost-effective method and does not require complicated nanolithography process for fabricating desired nanogaps in a reproducible fashion.